Predictors of mid-term prognosis and adverse factors in acute pulmonary embolism. (August 2017) - Liu, Xin; Chang, Suchi; Fu, Cuiping; Huo, Zhirong; Zhou, Jing; Liu, Chengying; Li, Shanqun; Sun, Aijun
Background: To explore the differences in short and middle term adverse factors of pulmonary embolism (PE) outcome. Methods: This was a single-center retrospective study of inpatients admitted from Zhongshan Hospital, Fudan University, with first-time PE. Clinical data were collected from patients with objectively confirmed PE, and a 2-year follow up was conducted. Results: The sample contained 310 patients with PE, ranging in age from 18 to 86 years old (mean 63.28 ± 15.30) and including 165 men (53.2%) and 145 women (46.8%). Successful treatment was achieved in 285 cases (91.9%) and unsuccessful treatment turned out in 25 cases (8.1%). Logistical regression analysis showed that massive PE [odds ratio (OR) = 23.625, 95% confidence interval (CI) 6.248–89.333], hypoxemia (OR = 11.915, 95% CI 1.900–74.727), leukocytosis (OR = 9.120, 95% CI 2.227–37.349) and active cancer (OR = 6.142, 95% CI 1.233–30.587) were associated with a poor prognosis for acute PE in the short term (in hospital). Seventy-seven PE cases with complete electronic records were finally included in the follow up. Cox regression analysis showed that elevated pulmonary artery systolic pressure (PASP, ⩾50 mmHg) (HR = 9.240, 95% CI, 2.307–37.013) and active cancer with PE (HR = 3.700, 95% CI, 1.010–13.562) were associated with an increased risk of mid-term mortality after a follow-up period of 2 years. Conclusions: Massive PE, hypoxemia, leukocytosis and active cancer may contribute to a poor prognosis for patients with acute PE in hospital. Elevated PASP and active cancer may negatively impact survival time and increase the risk of death for patients with acute PE after 2-year follow up. Short-term adverse factors of acute PE are not exactly the same as the mid-term risk factors of acute PE.